Inconsistent Responding in a Criminal Forensic Setting: An Evaluation of the VRIN-r and TRIN-r Scales of the MMPI–2–RF. Issue 3 (4th May 2017) - Gu, Wen; Reddy, Hima B.; Green, Debbie; Belfi, Brian; Einzig, Shanah
ABSTRACT: Criminal forensic evaluations are complicated by the risk that examinees will respond in an unreliable manner. Unreliable responding could occur due to lack of personal investment in the evaluation, severe mental illness, and low cognitive abilities. In this study, 31% of Minnesota Multiphasic Personality Inventory–2 Restructured Form (MMPI–2–RF; Ben-Porath & Tellegen, 2008/2011) profiles were invalid due to random or fixed-responding (T score ≥ 80 on the VRIN–r or TRIN–r scales) in a sample of pretrial criminal defendants evaluated in the context of treatment for competency restoration. Hierarchical regression models showed that symptom exaggeration variables, as measured by inconsistently reported psychiatric symptoms, contributed over and above education and intellectual functioning in their prediction of both random responding and fixed responding. Psychopathology variables, as measured by mood disturbance, better predicted fixed responding after controlling for estimates of cognitive abilities, but did not improve the prediction for random responding. These findings suggest that random responding and fixed responding are not only affected by education and intellectual functioning, but also by intentional exaggeration and aspects of psychopathology. Measures of intellectual functioning and effort and response style should be considered for administration in conjunction with self-report personality measures to rule out rival hypotheses of invalid profiles.